Clinical companion for medical-surgical nursing: concepts for interprofessional collaborative care - Ignatavicius, Donna D.; Workman, Linda (Author); Rebar, Cherie R. (Author); Heimgartner, Nicole M. (Author) (Philadelphia Elsevier Saunders, 2021)
Make this thoroughly updated, concise guide your go-to reference for medical-surgical clinicals! Corresponding to Medical-Surgical Nursing: Concepts for Interprofessional Collaborative Care, 10th Edition, from Ignatavicius, Workman, Rebar, and Heimgartner, the Clinical Companion is an easy-to-use, A-to-Z guide to more than 250 common medical-surgical conditions and their management. This portable resource features a strong focus on the Concepts and Exemplars identified in the "Iggy" textbook, along with updated content cross-referenced to the main text. Emphasizing interprofessional collaborative care, this clinical companion is sure to become your most trusted clinical reference. UNIQUE! Concepts for Interprofessional Collaborative Care section reflects the emphasis on Concepts in the Ignatavicius textbook and provides students with a quick reference to essential nursing and health Concepts for effective clinical practice. A-Z synopses of more than 250 diseases and disorders - along with related interprofessional collaborative care - serve as a quick reference for clinicals and a study resource for essential medical-surgical content. UNIQUE! QSEN highlights focus on one or more of the six core QSEN competencies (patient-centered care, teamwork and collaboration, evidence-based practice, quality improvement, safety, and informatics) to help students understand how to apply QSEN competencies for safe, effective care. UNIQUE! Focus on interprofessional collaboration provides tips for coordinating care with other health professionals. UNIQUE! Nursing Safety Priorities boxes (Drug Alert, Critical Rescue, and Action Alert) reinforce critical safety measures at the bedside and mirror those in the Ignatavicius textbook. Printed thumb tabs appear along the edges of the pages for quick access to clinical information and just-in-time learning and reference on the job
Section I: Concepts for Interprofessional Collaborative Care Section II: Diseases and Disorders: Alphabetical entries for more than 250 common Exemplar and non-Exemplar disorders
Section I: Concepts for Interprofessional Collaborative Care Section II: Diseases and Disorders: Alphabetical entries for more than 250 common Exemplar and non-Exemplar disorders
Keywords: Nursing; Nursing Handbooks, manuals, etc